2000
DOI: 10.1109/94.839346
|View full text |Cite
|
Sign up to set email alerts
|

PD pattern analysis during induced test of large power transformers

Abstract: The partial discharge (I'D) aeasureinei~ts on powcr transfortncrs arc studied with IZ view toward discrimination and claasificatioii of diffcrcirt discliargc sonrccs. For this purposc digital analysis is applied to power transformers and renctois going through acceptance testing. Furthermore, based OH these measurements, PU databases havc been developed to support thc discharge evaluation during iiiduced voltage tests of transformers. Using this technique, a clear distinction is possible betwecn iransforiiwrs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…10, and [48]). These HV apparatus are not discharge free and in general a discharge level 500 pC is tolerated.…”
Section: H Partial Dischargementioning
confidence: 96%
“…10, and [48]). These HV apparatus are not discharge free and in general a discharge level 500 pC is tolerated.…”
Section: H Partial Dischargementioning
confidence: 96%
“…Most of the research was done by Fromm [16][17][18], Morshuis et al [19] and Gulski et al [20]. Fromm has built a model with parameters including discharge magnitude q i , time of discharge interval t i , and instantaneous voltage across the test object, which describes the stochastic discharge process at dc voltage.…”
Section: Introductionmentioning
confidence: 99%
“…PD behavior can be represented in various ways. Because of the randomization of PD activity, one of the most popular representations is the 3-D (ij-Q-N) distribution [2], [3], i.e., the PD pattern is described using a pulse count N versus pulse height Q and phase angle ij diagram. Previous experimental results have adequately demonstrated that ij-Q-N distributions are strongly dependent upon the PD source.…”
Section: Introductionmentioning
confidence: 99%